AN ECONOMIC ANALYSIS OF CAMPUS CRIME AND POLICING IN THE UNITED STATES: AN INSTRUMENTAL VARIABLES APPROACH - Joseph T. Crouse (European Scientific Journal, ESJ, 2014)
To date, the literature on campus crimes and its determinants has been largely descriptive and narrowly focused utilizing only regional crosssectional data. By examining the factors that influence campus crimes utilizing a national panel collected from the FBI’s Uniform Crime Report from 2000 to 2010, this paper helps to fill the under-researched aspect of how policing and campus setting influence campus crimes, both those of a violent and non-violent nature. Empirical evidence presented here suggests that there are significant differences in the effectiveness of policing by census region, by degree of urbanization, and by campus setting. Results suggest that the policing elasticities of crime are higher in the Northeast and Midwest than in the South and West. The nationwide campus policing elasticity suggests that a 10% increase in the campus police force would lead to a 10.5% to 17.6% decrease in campus crime.